Alteration in EEG Delta and Beta Power During Working Memory Performance Differentiates Patients with Parkinson’s Disease with and without Dementia - Anita Pal; Madhuri Behari; Ratna Sharma (Annals of Indian Academy of Neurology, 2024)
Background and Objectives: Working memory (WM) impairment is a common and progressive abnormality in Parkinson’s disease (PD), which ultimately leads to dementia. Individuals with PD exhibit altered electroencephalogram (EEG) patterns while engaging in tasks that require WM. The study examined the EEG patterns associated with WM maintenance in PD patients. Methods: The study consisted of two groups of PD patients with a sign of dementia (PDD) who had a Mini Mental State Examination (MMSE) score ≤24, PD patients with no sign of dementia (PDND) with an MMSE score >24, and a group of healthy individuals serving as controls (CON). We obtained EEG during a word memorization task using a 128-channel system. The spectral power of the EEG was computed using the fast Fourier transformation algorithm. Results: Compared to both PDND and CON groups, PDD group exhibited higher power in the delta and beta frequency bands. Conversely, there was a notable decrease in power in the gamma band in both the PDD and PDND groups compared to the CON group. In addition, the PDD group exhibited higher power in the gamma band compared to the PDND group. Power in the alpha (LA1, LA2, and UA) and theta bands was greater in PDND and PDD compared to CON, but was similar between PDND and PDD groups. Conclusion: While performing WM tasks, PDD exhibits increased delta and beta power. These findings can be used as a quantitative biomarker to evaluate the severity of initial WM impairments, which could potentially develop into dementia in the future.